2019
DOI: 10.2169/internalmedicine.2587-18
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hypotension Associated with Postural Tachycardia Syndrome

Abstract: Postural tachycardia syndrome (POTS) can cause orthostatic headache. However, it is difficult to differentiate POTS from spontaneous intracranial hypotension (SIH) caused by cerebrospinal fluid (CSF) leaks. We herein report a 53-year-old woman who presented with SIH associated with POTS. A cervicothoracic and lumbar epidural blood patch rapidly improved not only the headache but also the orthostatic tachycardia, suggesting POTS secondary to SIH. This case suggests that a CSF leak can cause secondary POTS. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Postural tachycardia syndrome has been described as a final common-end pathway for multiple different disorders. 30 It is seen with not only the aforementioned co-morbidities, such as concussion, autoimmune disease, and joint hypermobility, as well as being seen more in females and in Caucasians, but it is also associated with such diverse entities as mast cell activation syndrome, 31 median arcuate ligament syndrome, 32 Chiari malformation, 33 cervical instability, 34 cerebrospinal fluid leak, 35 and syringomyelia. 36 Once this disorder is better defined and established, we would expect to offer new hypotheses or better explanations as to why these family members experience increased associated medical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Postural tachycardia syndrome has been described as a final common-end pathway for multiple different disorders. 30 It is seen with not only the aforementioned co-morbidities, such as concussion, autoimmune disease, and joint hypermobility, as well as being seen more in females and in Caucasians, but it is also associated with such diverse entities as mast cell activation syndrome, 31 median arcuate ligament syndrome, 32 Chiari malformation, 33 cervical instability, 34 cerebrospinal fluid leak, 35 and syringomyelia. 36 Once this disorder is better defined and established, we would expect to offer new hypotheses or better explanations as to why these family members experience increased associated medical complications.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this study, all 9 patients with SIH had an increase in HR during HUTT and showed features of orthostatic intolerance. Kato Y et al 7 described an adult female having SIH associated with orthostatic intolerance. Orthostatic headaches in orthostatic intolerance is postulated to be due to relative CSF hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…5 International Classification of Headache Disorders (ICHD) third edition recommends treating patients with typical orthostatic headaches with no apparent cause and after exclusion of POTS with autologous lumbar epidural blood patch (EBP). 6 SIH and orthostatic intolerance may co-exist in adults 5,7 but have not been described in young patients. We report a series of seven young patients presenting with orthostatic headaches with an initial diagnosis of SIH and subsequently shown to have orthostatic intolerance on evaluating persistence of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a case series of 48 patients with POTS and 9 patients with SIH, all patients with SIH fulfilled the clinical criteria of POTS leading the authors to conclude that patients with POTS and orthostatic headache should be screened with further diagnostic tests for SIH [ 44 ]. Kato et al reported a patient with POTS and SIH whose SIH and POTS resolved after treatment with an epidural blood patch, suggesting that POTS may be secondary to SIH [ 45 ]. Using dynamic ultrasound of the optic nerve may differentiate between SIH and POTS based on the decreasing optic nerve sheath diameter upon standing in SIH, but not POTS [ 46 ].…”
Section: Pots and Intracranial Hypotensionmentioning
confidence: 99%